2018
DOI: 10.1590/1516-4446-2017-2476
|View full text |Cite
|
Sign up to set email alerts
|

Sexual compulsivity, anxiety, depression, and sexual risk behavior among treatment-seeking men in São Paulo, Brazil

Abstract: The data contribute to the field by providing information on men of all sexual orientations who are searching for mental healthcare. The connections among these psychopathological factors and sexual risk behavior have implications for public health, clinicians, and research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0
14

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 36 publications
3
8
0
14
Order By: Relevance
“…The fact that HD was proposed for inclusion in the DSM-5 (Kafka, 2010) made it natural to consider it the most appropriate clinical categorization of excessive sexual behavior at the time for the onset of this research project. The findings of Study I (Öberg et al, 2017) and the studies that have demonstrated the validity of the HD diagnosis in forensic and clinical samples (Kafka, 2014;Reid, Carpenter, et al, 2012;Scanavino et al, 2018), support this choice for clinical categorization. At the same time, we have acknowledged and encouraged the need for additional research on the condition.…”
Section: Is Hd a Suitable Categorization Of Excessive Sexual Behavior?mentioning
confidence: 71%
See 3 more Smart Citations
“…The fact that HD was proposed for inclusion in the DSM-5 (Kafka, 2010) made it natural to consider it the most appropriate clinical categorization of excessive sexual behavior at the time for the onset of this research project. The findings of Study I (Öberg et al, 2017) and the studies that have demonstrated the validity of the HD diagnosis in forensic and clinical samples (Kafka, 2014;Reid, Carpenter, et al, 2012;Scanavino et al, 2018), support this choice for clinical categorization. At the same time, we have acknowledged and encouraged the need for additional research on the condition.…”
Section: Is Hd a Suitable Categorization Of Excessive Sexual Behavior?mentioning
confidence: 71%
“…HD did not make any etiological claims in its formulation (Kafka, 2010(Kafka, , 2014Samenow, 2011), and was therefore a good starting point for sound and theoretically unbiased research. Although the results found in Study I (Öberg et al, 2017) and other studies on the validity of HD (Parsons et al, 2016;Scanavino et al, 2018;Scanavino et al, 2014) have suggested HD as an appropriate diagnostic category, it is important to remember that it is but one possible categorization. Through the newly included CSBD diagnosis in ICD-11 (Kraus et al, 2018;World Health Organization, 2018a, future studies on the complex of problems associated with excessive sexual behavior will surely lead to increased understanding of a salient psychiatric problem.…”
Section: Suggestions For Future Researchmentioning
confidence: 78%
See 2 more Smart Citations
“…La alta prevalencia de la infección por el VIH y el aumento de la probabilidad de comportamiento bisexual entre los HSH hace imperativo se comprenda el riesgo del VIH y las necesidades de prevención de los HSHM. La literatura muestra que a diferencia de los hombres con prácticas sexuales heterosexuales, los HSHM tienen menos probabilidad de participar en programas o actividades de prevención del VIH (Ellen et al, 2015;Friedman et al, 2014), más probabilidad que practiquen el sexo anal sin condón con parejas ocasionales (Grov, Golub, Mustanski, & Parsons, 2010), de buscar intencionalmente el sexo anal sin condón (Scanavino et al, 2018) y por ende, más posibilidad de adquirir el VIH (McCree et al, 2017).…”
unclassified